2009
DOI: 10.1007/s00134-009-1588-z
|View full text |Cite
|
Sign up to set email alerts
|

Six-month outcome in acute kidney injury requiring renal replacement therapy in the ICU: a multicentre prospective study

Abstract: ICU survivors from RRT for AKI have an impaired QOL at 6 months, but sustained autonomy in their daily lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 24 publications
8
41
1
3
Order By: Relevance
“…These patients were ∼7% worse concerning physical health, but 5% better concerning mental health compared with our data, thus confirming the general trend seen in our patients. Similar results were also seen by Delannoy et al 39 as early as 6 months after surviving AKI requiring RRT in the ICU. 39 Abelha et al 40 on the other hand indicated otherwise.…”
Section: Qolsupporting
confidence: 88%
See 1 more Smart Citation
“…These patients were ∼7% worse concerning physical health, but 5% better concerning mental health compared with our data, thus confirming the general trend seen in our patients. Similar results were also seen by Delannoy et al 39 as early as 6 months after surviving AKI requiring RRT in the ICU. 39 Abelha et al 40 on the other hand indicated otherwise.…”
Section: Qolsupporting
confidence: 88%
“…Similar results were also seen by Delannoy et al 39 as early as 6 months after surviving AKI requiring RRT in the ICU. 39 Abelha et al 40 on the other hand indicated otherwise. These authors investigated QoL by SF-36 ™ in patients 6 months after AKI.…”
Section: Qolsupporting
confidence: 88%
“…Two European studies used the Short Form Health Survey (SF-36) questionnaire to report QoL in ICU patients with AKI [8,9]. This assessment is also of global measures of health, covering eight health dimensions, of which mental health is just one, and the scores are aggregated.…”
Section: Discussionmentioning
confidence: 99%
“…Again, no assessment is made of the potential impact of events. One study [8] reported a reduction in QoL at six months, the other [9], which repeated the assessment at different time intervals, reported a reduction in three domains of the SF-36 for ICU patients with AKI compared with those without at ICU discharge, but this difference was no longer present at six months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation